(untitled) (Conferencea, 2024)
In this article, the activity of helping young people to acquire the necessary skills for the implementation of their constitutional rights and civic duties, active education of conscious respect for the state and legislation, which are national and civil democratic values in our country, is discussed in practice today. It is justified that it gives the result.